Strategi Kebijakan Moneter di Indonesia - Sriyono, Sriyono (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
Generally, monetary policy was a policy to achieve macroeconomic stability, as price stability, economic growth and the availability of employment. All target was difficult be executed because the tradeoff between variables. Indonesia after the monetary crisis changes its strategy of monetary policy by using the framework of targeting inflation. During the implementation of the policy strategy, the level of success was not satisfying so it needed to be reviewed whether the strategy used appropriate according to economic conditions in Indonesia.